2005
DOI: 10.1196/annals.1313.040
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Pemphigus Autoimmunoglobulins with Epidermal Cells: Activation of the Fas Apoptotic Pathway and the Use of Caspase Activity for Pathogenicity Tests of Pemphigus Patients

Abstract: Pemphigus is a fatal autoimmune disease in which autoimmunoglobulins PV-IgG (binding to desmoglein 3) and PF-IgG (binding to desmoglein 1) in pemphigus vulgaris and pemphigus foliaceus, respectively, cause intraepidermal blisters, cell-cell separation (acantholysis), and cell death. The mechanism of acantholytic lesion formation has not yet been elucidated. Recently, we have reported that an apoptotic mechanism might be operative in PV-IgG-induced acantholysis: (1) in patients' lesional and some perilesional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 21 publications
4
51
1
2
Order By: Relevance
“…Several groups (36)(37)(38)(39), including ours (15,16), have established that in the acantholytic process, an increase in the Bax/Bcl-2 ratio in addition to an increase in caspase activities may be detected in in vitro or in vivo studies. These findings, along with several reports demonstrating that upregulation of nNOS increases caspase activity (40)(41)(42) and the involvement of the Bcl-2-family members in caspase-dependent apoptosis due to increased NO (43)(44)(45), underline the possible implication of nNOS in promoting PV acantholysis.…”
Section: Discussionmentioning
confidence: 98%
“…Several groups (36)(37)(38)(39), including ours (15,16), have established that in the acantholytic process, an increase in the Bax/Bcl-2 ratio in addition to an increase in caspase activities may be detected in in vitro or in vivo studies. These findings, along with several reports demonstrating that upregulation of nNOS increases caspase activity (40)(41)(42) and the involvement of the Bcl-2-family members in caspase-dependent apoptosis due to increased NO (43)(44)(45), underline the possible implication of nNOS in promoting PV acantholysis.…”
Section: Discussionmentioning
confidence: 98%
“…Original immunohistochemical studies revealed Fas receptor (FasR) on KCs of lesional epidermis (26). Subsequent studies demonstrated that PVIgG binding to KCs causes secretion of soluble FasL, increased production and cellular amounts of FasR and FasL (soluble and membranal), co-aggregation of FasL and FasR with caspase 8 in a membranal deathinducing signaling complex, and down-regulation of the apoptosis inhibitor FLIP-l (5,10,11,14,27,28). The keratinocyte FasR can be also triggered by FasL expressed by the cytotoxic T cells (29) found in the skin of PV patients (30).…”
Section: Pemphigus Vulgaris (Pv)mentioning
confidence: 99%
“…15 More recently, determination of caspase 3 activity in the HaCaT culture treated with PVIgG has been proposed as a test for pathogenic activity of the autoantibodies. 16 It is now well established that intravenous immunoglobulin (IVIg) therapy is an effective treatment modality of PV, 17,18 but the mechanism of therapeutic action of IVIg has not been fully elucidated. The IVIg drug contains purified preparations of immunoglobulins from plasma of healthy human donors, containing predominantly polyclonal IgG, and various immunomodulatory contaminants.…”
mentioning
confidence: 99%